Transformation of the magazine «Aqiqat» («Communist of Kazakhstan») in a new era - Yermaganbetova, Z.N.; Aitbaeva, A.E.; Abdrazakova, A.K. (Bulletin of L.N. Gumilyov Eurasian National University. JOURNALISM Series, 2023)
In any period, periodicals were able to be a mirror of true life. From the journalistic works published in it, we know the face of that period, the history of the time. The article will talk about the face of the magazine «Aqiqat» («Communist of Kazakhstan») in the years of reconstruction. The author analyzed materials and scientific articles reflecting changes in the development of society at that time, especially in the fields of politics, history, culture, literature, art, etc. The research tells about the editors who contributed to expanding the topic of the publication, raising the theoretical and cognitive level, and the outstanding Kazakh writers who actively participated in the magazine and left behind a rich legacy with their exemplary work. The editorial skill of Kakimzhan Kazybayev in enriching the content of the magazine during the years of reconstruction is especially appreciated. The aim of the scientific research is to determine the role of the publication in the development of Kazakh journalism, which has been forming together with the history of the country. In the years of reconstruction, he paid attention to the specifics of the genre, showing with concrete examples that he gave voice to the actual problems of his period. The author reviews the contents of the party journal of the Soviet period. Conclusions are made about the creative search of the magazine, which has turned to a new direction, to satisfy the needs of the readers. In the course of writing the article, the methods of studying and systematizing, analyzing, and summarizing theoretical materials were used.